Convolution and Correlation Forms for the Offset Coupled Fractional Fourier Transform - Nasrullah; Wahyuni Ekasasmita; Nurwahidah (Universitas Islam Negeri Alauddin Makassar, 2025)
This work presents convolution and correlation in offset coupled fractional Fourier transform. The offset coupled fractional Fourier transform can be regarded as a generalized version of the coupled fractional Fourier transform. Various properties including this work like inversion formula and Parseval are studied in general and in detail for the offset coupled fractional Fourier transform. In addition, the relationship with two-dimensional Fourier transform and the offset coupled fractional Fourier transform.